Alkylation catalyzed by H2SO4: Promoting effects of ASO on the solubility of isobutane in acid phase. (15th October 2022) - Xin, Yangyang; Hu, Yufeng; Wang, Yichuan; Jiang, Siqi; Li, Mengchen; Chi, Kebin; Zhang, Shang; Gao, Fei; Ren, Chunxiao; Zhang, Shuai; Ma, Chenglong
Graphical abstract: Highlights: The addition of ASO compounds obviously promotes the isobutane solubility in H2 SO4 . Paraffins and cycloparaffins have better solubilization of isobutane. Cycloparaffins can be selected as excellent co-catalyst for alkylation. Cycloparaffin co-catalyst markedly enhanced the quality of alkylates. Cycloparaffin co-catalyst significantly reduced the consumption of catalyst. Abstract: For alkylation catalyzed by H2 SO4, the promotion of solubility of isobutane in H2 SO4 is of major importance to the enhancement of quality of alkylates. ASO (acid-soluble oils or conjunct polymers or red oil) are the potential co-catalyst to improve the solubility of isobutane and to optimize the interfacial characteristics of acid/hydrocarbon dispersions. On the basis of the calculation results of COSMO-RS method, we found that the solubility of isobutane in H2 SO4 was obviously increased upon the addition of most ASO molecules. Moreover, a better dissolution of isobutane in H2 SO4 can be achieved by adding the hydrocarbons like paraffins and cycloparaffins into H2 SO4 . On the basis of these findings, two cycloparaffins were selected and used as the co-catalyst (the co-catalysts A and B) to improve the performance of the H2 SO4 catalyst. The alkylation results showed that these cycloparaffins enhanced the quality of alkylates. In particular, upon the addition of the co-catalyst B, the RON (research octane number) value, the TMP/DMH (trimethylpentane/dimethylhexane) ratio, and the contents of C8 and TMP (trimethylpentane) were increased significantly from 92.67 and 6.51, 68.25% and 59.10% to 94.38 and 6.97, 74.81% and 65.34%, and the consumption of the H2 SO4 catalyst was reduced by 38%.